Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006923.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Regular treatment with formoterol for chronic asthma: serious adverse events

Abstract: In comparison with placebo, we have found an increased risk of serious adverse events with regular formoterol, and this does not appear to be abolished in patients taking inhaled corticosteroids. The effect on serious adverse events of regular formoterol in children was greater than the effect in adults, but the difference between age-groups was not significant.Data on all-cause serious adverse events should be more fully reported in journal articles, and not combined with all adverse events or limited to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 182 publications
0
30
0
Order By: Relevance
“…Moreover, as the mechanism has an immune basis involving the aberrant activation of STAT6, our findings further explain the ability of glucocorticosteroids when added to salmeterol to mask in part this untoward effect. Interestingly, addition of glucocorticosteroids to formoterol does not necessarily mask the pro-asthmatic potential, and thus morbidity, of this LABA [ 15 ], nor is it clear that addition of glucocorticosteroids entirely block the pro-asthmatic potential of salmeterol with long-term use [ 14 ]. Our data further support these observations because although glucocorticosteroids have a clear anti-asthmatic effect ( Fig 1C ), LABAs activate STAT6 even in the presence of glucocorticosteroids and are alone sufficient to induce asthma-like airway obstruction in the complete absence of allergen provocation ( Fig 1D and 1H ; S3 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the mechanism has an immune basis involving the aberrant activation of STAT6, our findings further explain the ability of glucocorticosteroids when added to salmeterol to mask in part this untoward effect. Interestingly, addition of glucocorticosteroids to formoterol does not necessarily mask the pro-asthmatic potential, and thus morbidity, of this LABA [ 15 ], nor is it clear that addition of glucocorticosteroids entirely block the pro-asthmatic potential of salmeterol with long-term use [ 14 ]. Our data further support these observations because although glucocorticosteroids have a clear anti-asthmatic effect ( Fig 1C ), LABAs activate STAT6 even in the presence of glucocorticosteroids and are alone sufficient to induce asthma-like airway obstruction in the complete absence of allergen provocation ( Fig 1D and 1H ; S3 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Our two previous reviews Cates 2008a) indicated an increase in all-cause SAEs when both regular formoterol and regular salmeterol were compared with placebo. It would require very large numbers of patients in head-to-head comparison trials to determine whether there is any difference in SAEs between regular formoterol and salmeterol, and it is perhaps not surprising that it has not been possible to draw conclusions from this review, as the number of participants in the included trials is relatively small.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 93%
“…Two published reviews have assessed the risk of serious adverse events (SAEs) with regular salmeterol and formoterol (Cates 2008a) without randomised inhaled corticosteroids in comparison to placebo or short-acting beta 2 -agonists, and further reviews have compared regular formoterol and salmeterol when randomised with an inhaled corticosteroid Cates 2009a;Jaeschke 2008a).…”
mentioning
confidence: 99%
“…Other asthmatics may benefit from vaccination, although it does not appear to protect from asthma exacerbations or improve asthma control (Evidence B). [107109]…”
Section: Approach To Asthma Managementmentioning
confidence: 99%